Tinjauan Yuridis Pemberian Insentif dalam Rangka Mendorong Percepatan Battery Electric Vehicle (BEV): Potensi Dukungan pada Greenwashing Dibalik Solusi Persoalan Lingkungan - Amiradiaty Nasution; Hauna Tsabitul Azmi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The Indonesian government issued Presidential Regulation Number 79 of 2023, amending Presidential Regulation Number 55 of 2019, to accelerate the adoption of battery-based electric vehicles (BEVs) and reduce greenhouse gas emissions through incentives. These incentives, both fiscal and non-fiscal, aim to encourage the public to switch to electric vehicles. However, the environmental impact of electric vehicles needs consideration in the context of sustainable transport. This study analyzes the challenges of the incentive policy in promoting BEVs and its potential connection to greenwashing practices, aiming to develop effective solutions for environmental issues related to these incentives. Using a normative juridical approach, the research relies on secondary data, including primary legal materials and secondary sources like textbooks, journals, expert opinions, and jurisprudence. The findings highlight the need for supervision in providing incentives and suggest prioritizing the electrification of public vehicles to achieve sustainable green transportation. Additionally, the study emphasizes strengthening non-motorized and electricity-based public transportation modes and transitioning to renewable energy sources to mitigate environmental impacts.